PESAN PERSUASIF "ALASAN MENIKAH 16 TAHUN" YOUTUBE ADHIGUNA DAN SABRINA PADA MINAT REMAJA - Selly Ramadhanti Rukmana (2021)
PERSUASIVE MESSAGE "Alasan Menikah Umur 16 Tahun" YOUTUBE ADHIGUNA AND SABRINA ON TEEN INTEREST SELLY RAMADHANTI RUKMANA Abstract Seeing the high number of early marriages in Indonesia, according to KPAI from the mass media many consider that the content about the romanticization of young marriage is one of the persuasive messages on the content of "Alasan Menikah Umur 16 Tahun" on Youtube Adhiguna and Sabrina who became the government's obstacle in lowering the number of early marriages, as well as the existence of new rules on the age of marriage for women that is 19 years (Law No.6 of 2019). The purpose of the research was to prove the existence and the influence of persuasive messages "Alasan Menikah Umur 16 Tahun" Youtube Adhiguna and Sabrina on the interest of marriage in teenagers. The approach used in the study was a quantitative survey that tested SMCR Theory on Youtube subscribers Adhiguna and Sabrina as many as 100 people. Sample techniques used Purposive Sampling while data processing using questionnaires. Persuasive messages are measured based on massage dimensions according to Berlo's communication model while interest is measured based on two (2) dimensions that are cognitive, and affective. The results of the Correlation Test showed a significance value of 0.000 which indicates a correlation because it lies in the <0.05. The calculated r coefficient of 0.795 indicates that there is a strong correlation. The results of a simple linear regression test showed that the persuasive message direction of "Alasan Menikah Umur 16 Tahun" on Youtube Adhiguna and Sabrina on adolescent interest is positive. The coefficient of determination showed that there was a 63.2% influence between the persuasive message "Alasan Menikah Umur 16 Tahun" on Youtube Adhiguna and Sabrina on adolescent interests. The results were reinforced by the results of hypothetical tests stating that Ho was rejected and Ha accepted, meaning there was an influence between the persuasive message "Alasan Menikah Umur 16 Tahun" on Youtube Adhiguna and Sabrina on the interests of teenagers. The conclusion of the study was the persuasive message "Alasan Menikah Umur 16 Tahun" on Youtube Adhiguna and Sabrina influenced the interest of teenagers, especially in Youtube subscribers Adhiguna and Sabrina. Keywords: Persuasive Message, Youtube, Interest, SMCR Theory by Berlo